Role of Acupuncture in the Treatment or Prevention of Migraine, Tension‐Type Headache, or Chronic Headache Disorders. Issue 7 (13th July 2016) - Coeytaux, Remy R.; Befus, Deanna
Abstract : Objective: To summarize the current evidence that evaluates the effectiveness of acupuncture for the treatment or prevention of migraine, tension‐type headache, and chronic headache disorders. Methods: Findings from selected systematic reviews and meta‐analyses are summarized. Results: Recently published systematic reviews and meta‐analyses demonstrate that acupuncture is associated with improved clinical outcomes compared to routine care only, medical management, and sham acupuncture 2 months after randomization. The evidence in support of acupuncture's comparative effectiveness at longer follow‐up periods is mixed. Cost effectiveness analyses conducted in the United Kingdom and Germany suggest that acupuncture is a cost‐effective treatment option in those countries. There are few or no cost‐effectiveness studies of acupuncture in the United States. Discussion: This brief review of the current, published evidence does not include a discussion of potential risks or adverse events associated with acupuncture. There is also the question of the extent to which placebo effects might contribute to acupuncture's clinical effectiveness. From a purely comparative effectiveness perspective, however, the evidence from clinical trials and meta‐analyses makes a compelling case in support of a potentially important role for acupuncture as part of a treatment plan for patients with migraine, tension‐type headache, and several different types of chronic headache disorders.